2016
DOI: 10.19045/bspab.2016.50085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt stress on some morphological and biochemical characteristics of sunflower (Samsung-600)

Abstract: Salinity in the growth medium causes significant reduction in plant growth parameters like leaf area, leaf length, root and shoot dry weight etc. The present study was conducted to assess the effect of salt stress on morphological and biochemical characteristics of sunflower. The hybrid (Samsung-600) seeds were grown under normal and saline conditions. The plants were treated with different doses of sodium chloride. Salt stress significantly reduced plant height, number of leaves, fresh and dry plant weight. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…(Table 2). Adverse effects of salt stress on leaf area of sunflower have also been reported by several authors (Rivelli et al, 2010;Achakzai et al, 2015;Khan et al, 2016).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…(Table 2). Adverse effects of salt stress on leaf area of sunflower have also been reported by several authors (Rivelli et al, 2010;Achakzai et al, 2015;Khan et al, 2016).…”
Section: Resultssupporting
confidence: 65%
“…However, it was reported that one of the reasons of dry matter decrease in sunflower cultivars was salt stress (Rivelli et al, 2010;Maia et al, 2016;Khan et al, 2016). The highest water content was observed in the cv.…”
Section: Resultsmentioning
confidence: 97%
“…12.3%, whereas control showed 7%. The result is in agreement to those of [11] in that respect that they performed an experiment of salinity stress against Lycopersicon esculentum Mill. Their result showed that Increasing of salinity resulted in increasing of soluble proteins in stem and leaf.…”
Section: Protein Contentssupporting
confidence: 91%
“…In several regions of the world, salinity stress may occur due to Na + and Clwhich may be greater than those of other salts present in the soil or water [14]. Salinity showed significant reduction at different stage of the species of Ocimum basilicum, petroselinum hortense, sweet marjoram and thymus maroccanus [15,16].…”
Section: Introductionmentioning
confidence: 99%